Simulações de plasma e eletromagnéticas de transmutador isotrópico - Daniel Moreira Coelho (2018)
This study presents an engineering design of an isotopic transmutative cell generator for tecnthium-99m. In order to analyze and choose the materials and the appropriate geometry, previous studies of NRI Group (Nucleus for Ionizing Radiation at UFMG NRI/UFMG) were considered and a model was developed for the simulation of these systems. The studied system consists of a microwave antenna, resonant cavity and target, which compound the nucleus of the neutrons generator. A model for electromagnetic and plasma simulation was developed to analyze the capacity of this device. The capacity of this device depends on the efficiency of the neutron generator measured by the neutron flux, which is dependent on the energy and flux of ions reaching the target. Among the modeling and simulation methods, were employed open software sources for the transmuting cell, aiming to evaluate resonant cavity and for complementary physical analysis. In addition, was evaluated the electromagnetic fields generated as a function of the resonant cavity geometry and the antenna frequency. The titanium target was designed based on other studies of the NRI Group. Deuterium plasma with a density 1016 particles/m³ was proposed with a frequency 0.898 GHz, using a microwave antenna of 2.45 GHz. Deuterium gas was used as ionic source. The different interactions of the electric, magnetic and ionic fields generated in the plasma were simulated. Also the antenna, the resonant cavity with its vibrational modes, the electric and magnetic field distribution, the ion density in the cavity for a specific power, the extraction of the ions from the cavity An ion generation rate was obtained in a period of 1s time from 3.12 1011 ions/s accelerated at 200 keV. It is possible to conclude that the investigated electromagnetic and plasma characteristics of the transmuting cell have shown that this generator has a remarkable potential that can support the generation of radioisotopes applied to the medical diagnosis.